Optimization IPAS Learning Outcomes through the Snowball Throwing Model Based on Animated Media among Elementary School Students - Theresyam Kabanga'; Jesika Jesika (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the effectiveness of integrating the Snowball Throwing cooperative learning model with animated video media to improve learning outcomes in Integrated Natural and Social Sciences (IPAS) among elementary school students. The approach addresses low engagement and underachievement in IPAS learning under the Merdeka Curriculum. A two-cycle Classroom Action Research (CAR) was conducted with 13 fourth-grade students at UPT SDN 4 Makale Selatan. Instruments included observation sheets, interviews, and a validated IPAS achievement test. Data were analyzed using descriptive statistics, paired-sample t-tests, Cohen’s d, and normalized gain (N-Gain). Student performance improved significantly from Cycle I (mean = 66.92; mastery = 46.15%) to Cycle II (mean = 80.76; mastery = 92.30%). Statistical analysis showed a significant effect (t(12) = 6.24, p .001) with a large effect size (d = 1.73) and moderate-to-high learning gain (N-Gain = 0.62). Improvements were also observed in students’ engagement, reasoning, and collaborative skills. The results demonstrate that combining Snowball Throwing and animated videos creates a student-centered, interactive learning environment. Animated media served as cognitive scaffolds, while the cooperative model fostered active inquiry and peer interaction. This integration aligns with social constructivist principles and supports 21st-century competencies, particularly critical thinking and collaboration.